2013
DOI: 10.1007/s40137-013-0035-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Molecular Markers for Cytologically Indeterminate Thyroid Nodules to Optimize Surgical Management

Abstract: The management of thyroid nodules with indeterminate cytology has traditionally been diagnostic thyroidectomy. However most nodules are benign, and for nodules that demonstrate histologic malignancy, two-stage thyroidectomy may be necessary. Molecular markers have emerged as an adjunct to preoperative FNAB cytology evaluation that can improve diagnostic accuracy. In this review, we discuss the latest methodologies and review diagnostic performance parameters of recent molecular marker techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…5 The high performance of a similar molecular panel was also validated by Cantara et al 16 In a subsequent cohort study, we observed that a clinical algorithm that used molecular testing results to guide extent of thyroidectomy led to a 30% increase in appropriate total thyroidectomy for a clinically significant TC while also resulting in a 33% increase in lobectomy alone for either papillary thyroid microcarcinoma or benign histology. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The high performance of a similar molecular panel was also validated by Cantara et al 16 In a subsequent cohort study, we observed that a clinical algorithm that used molecular testing results to guide extent of thyroidectomy led to a 30% increase in appropriate total thyroidectomy for a clinically significant TC while also resulting in a 33% increase in lobectomy alone for either papillary thyroid microcarcinoma or benign histology. 6 …”
Section: Discussionmentioning
confidence: 99%
“…4,13 Thyroidectomy was performed algorithmically for clinical, radiographical, cytological, and molecular results as previously described. 6 Extent of lymphadenectomy was determined by assessment of malignancy potential on preoperative ultrasonography and by intraoperative findings. Lateral compartment (levels 2–5) lymph nodes with suspicious ultrasound features including rounded appearance, cystic changes, loss of fatty hilum, and/or microcalcifications were biopsied preoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Two of twenty seven conventional PTC had coexistent BRAF V600E with p53 and/or PIK3CA mutations which are typically more characteristic of aggressive thyroid cancers. The identification of more than one driver mutation may provide preoperative prognostic information that may beneficially guide surgical management .…”
Section: Genetic Mutations and Rearrangementsmentioning
confidence: 99%